Rate effects in a proportional counter with resistive cathode - Bueno, Carmen C. (1998)
In this work, the rate effects associated with the gain of detectors with resistive electrodes are considered. To study these effects it was decided to use the classical proportional counter geometry, with a cylindrical glass tube as the cathode, rather than parallel plate devices. Indeed, the generality of the information obtained is not affected and the cylindrical proportional counter geometry has several advantages to gather detailed experimental data and to compare it with simple electric field calculations. A self-consistent set of data is presented for the effects of counting rate from a few tens of Hz up to several hundreds of Hz, using several gas mixtures, different anode wires, cathode radii and thickness of the resistive electrodes. Although a few sources of systematic errors can be identified, all the observed experimental data can be quantitatively explained. Indeed, the measured gas amplification, from a few tens up to ~5×104 and for the range of counting rates quoted above, depends only on the local electric field as it should be expected. These results are directly relevant to approach the problem of counting efficiency in resistive plate chambers.